Hubungan Antara Lingkungan Belajar yang Mendukung Kebutuhan dan Perilaku Sabotase Diri Akademik pada Siswa Form Two di Meru County, Kenya - Kabira, Judith Kamathi; Mugambi, Doyne Kageni; Wawire, Chrispus Koinange; Ireri, Anthony Muriithi (Faculty of Psychology, Universitas Surabaya, 2025)
Academic self-sabotaging behavior is a prevalent problem among Form Two students in Kenya, being linked to lower academic achievement, academic anxiety, academic stress, and poor mental health. Existing research has consistently linked basic psychological needs (BPN) satisfaction to less academic self-sabotaging behavior. Despite this, there is a relative dearth of studies exploring this area in the Kenyan context. Therefore, the current study examined how basic psychological needs-supportive learning environment relate to academic self-sabotaging behavior, with self-determination theory (SDT) as the theoretical basis, and a convergent parallel mixed-methods research design. The quantitative study sample comprised 400 students (215 boys; 185 girls) drawn using proportionate stratified and simple random sampling. The qualitative study sample included 20 students drawn using purposive criterion sampling. Data for quantitative study was collected using Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS; Chen et al., 2015) and Academic Self-Handicapping Scale (Midgley & Urdan, 2001). Qualitative data collection tools was a semi-structured interview schedule. Study results revealed a weak, negative and statistically significant correlation between needs-supportive learning environment and academic self-sabotaging behavior (r(396) = - .14; p < .01). Qualitative findings complemented these results, revealing that a learning environment that supported students’ needs of autonomy, competence, and relatedness promoted high level of adaptive learning behaviors. The study recommends that schools should promote an autonomy-supportive school environment that meets students’ basic psychological needs (BPN) to reduce academic self-sabotaging behavior.